Strategi Produser TVRI NTB Dalam Penyajian Berita Pada Tayangan Dialog Sudut Pandang - I Gusti Ayu Djulia Guswina; Rieka Yulita Widaswara; I Ketut Putu Suardana (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2022)
This research was conducted with the aim of finding out how the TVRI west nusa tenggara producer's strategy in presenting news on the Sudut Pandang dialogue shows the background of the number of viewers the Sudut Pandang dialogue shows an average of less than 20 viewers per day on YouTube, so researchers are interested in examining how the strategy Producer in presenting the Sudut Pandang dialogue news program on TVRI station. This study uses nonparticipatory observation methods, interviews and documentation with a descriptive qualitative approach. In this study, an analysis was carried out using interpersonal communication theory with a triadic communication pattern based on the concept of Pontoh and Novinati to TVRI Producers in presenting news on the Sudut Pandang dialogue. The results of this study are that the producer has a strategy in presenting news on Sudut Pandang where the first strategy is to make the theme as interesting as possible, maintain communication with colleagues and lastly continue to evaluate to find out the obstacles that occur. The producer's strategies are in accordance with the strategic concept, namely the planning stage, the production stage, and the evaluation stage. With these strategies, it is hoped that Producers will be able to develop new strategies that can increase the audience's interest in watching the Sudut Pandang dialogue.